Pedestrian Safety Initiative in Montgomery County, Maryland: Data-Driven Approach to Coordinating Engineering, Education, and Enforcement. Issue 1 (January 2014) - Dunckel, Jeff; Haynes, William; Conklin, Joana; Sharp, Susan; Cohen, Alexandra
The Pedestrian Safety Initiative in Montgomery County, Maryland, which was introduced in 2007, uses a data-driven approach to coordinate engineering, education, and enforcement to create a more pedestrian-friendly, walkable environment. From the geographic information system and data analysis of countywide pedestrian crashes from 2004 to 2008, 10 areas with a high incidence of pedestrian crashes were identified. Engineering, education, and enforcement programs targeted these 10 high incidence areas (HIAs). Pedestrian road safety audits were conducted at the HIAs to determine the most effective engineering improvements for each area. Traffic and pedestrian calming measures were subsequently implemented at these locations. Demographic analysis grouped the HIAs together to create more effective education campaigns, and community members were involved to reach a wider audience. Enforcement efforts targeted pedestrians and drivers in the HIAs with warnings and citations for those who violated pedestrian laws. Similar methodology has been used to target HIAs near schools as part of the initiative's Safe Routes to School program. This holistic Three E Approach (engineering, education, and enforcement) is continuously being refined to reflect emerging data trends in pedestrian collisions. Between 2009 and 2012, pedestrian collisions in the treated HIAs dropped 43%, pedestrian fatalities countywide dropped 38% from 2008 to 2012, and pedestrian collisions in a subset of the Safe Routes to School areas dropped 79%.